Improving the laboratory diagnosis of pyruvate kinase deficiency. (2nd May 2021) - Laas, Claire; Lambert, Christopher; Senior McKenzie, Tania; Sheldon, Ewart; Davidson, Philip; Rees, David; Clark, Barnaby
Summary: Pyruvate kinase (PK) deficiency is an autosomal recessive disease caused by mutations in the PKLR gene, which reduce erythrocyte PK enzyme activity and result in decreased energy synthesis in red cells, causing haemolytic anaemia. Historically, the investigation into pyruvate kinase deficiency (PKD) has been led by a red cell enzyme assay determining PK enzyme activity per unit of haemoglobin. For our laboratory, the reference range was set by Beutler et al . in 1977 when the test was first established. The introduction of genetic testing permitted the creation of reference sample datasets, with positive controls having two pathogenic variants causing disease. This permitted re‐assessment of the enzyme assay's sensitivity and specificity, and was used to reassess the reference range of the enzyme assay. Using sequenced samples, we have devised an enzyme assay, DNA testing workflow, which minimises false negative/positive results and improves the diagnostic efficiency. This combined enzyme‐DNA testing strategy should improve the diagnostic accuracy whilst limiting the number of expensive DNA tests. During this evaluation, 10 novel genetic variants were identified and are described.